IMPLEMENTATION OF PEKASAM NEW INNOVATIVE PRODUCT TECHNOLOGY IN PENUKAL ABAB DISTRICT LEMATANG ILIR DISTRICT - Defriyanti, Wenni Tania (Program Studi Teknologi Pangan, 2019)
Fish is one of the sources of animal protein that many people consume because it is relatively easy to obtain and the price is affordable. Because of the many fish there are, so we need a way to preserve them. One way that has been done is by developing fish processed products. The purpose of developing processed fish products is to process river / freshwater fish into long-lasting processed products, and to find out the types of good packaging for the shelf life of processed fish products. Sampling was carried out in Air Itam Village, PALI Regency, on the SMEs that make stir-fry and non-stir-fry pekasam. The method used is a laboratory test method to determine microbiological tests (Total Plate Figures), and determination of pH. From the test results it can be seen that stir-fried pekasam is not suitable for direct consumption with a shelf life of more than 5 days if stored at room temperature when viewed from the number of bacteria and fungi that have passed the standard food standard, but if it is reprocessed before consumption (sauteed) it may still be feasible because some bacteria and fungi that can't stand the heat will die. Saute Pekasam is not suitable for consumption with a shelf life of more than 5 days if stored at room temperature (because the sample is tested after 5 days of manufacture, the sample is not tested on Day 0 to Day 5, which may still be fit for consumption before day 5 ). In order to produce processed fish products in the form of durable pekasam, the process of making pekasam can be done hygienically so that it can inhibit the growth of bacteria and fungi.